Evaluation of Mobile Academic Information System with Notifications Using Heuristic Evaluation and WCAG-EM - Nugraha, I Gede Pradipta Adi; Indrawan, Gede; Asroni, Ahmad; I Gede Aris Gunadi (Sinkron : jurnal dan penelitian teknik informatika, 2025)
SIsKA-NG Mobile is a mobile information system that provides specific information related to students’ study activities in the Computer Science Study Program at Universitas Pendidikan Ganesha. This newly developed application has never been evaluated. Therefore, it is necessary to evaluate the accessibility and interface for improvement. This study focuses on the analysis related to the application accessibility of partial color blindness users, using the WCAG-EM method and the heuristic evaluation method. Based on the accessibility evaluation results on the first development, it was found that SIsKA-NG mobile did not fully meet the standards of the mobile application, while based on the results of the heuristic evaluation, it was found 24 problems, where 8 problems with the highest severity rating (Catastrophic), 7 problems with high priority (Major), and others related to low priority (Minor) problems and insignificant problems. The subsequent development to enhance the quality of the interface and accessibility of SIsKA-NG Mobile used those findings as a reference so that this application can meet the needs of all users more effectively and inclusively.